2018
DOI: 10.20944/preprints201803.0057.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fault-Tolerant Control for ROVs Using Control Reallocation and Power Isolation

Abstract: This paper describes a novel thruster fault-tolerant control system (FTC) for open-frame remotely operated vehicles (ROVs). The proposed FTC consists of two subsystems: a model-free thruster fault detection and isolation subsystem (FDI) and a fault accommodation subsystem (FA). The FDI subsystem employs fault detection units (FDUs), associated with each thruster, to monitor their state. The robust, reliable and adaptive FDUs use a model-free pattern recognition neural network (PRNN) to detect internal and exte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This table also has shown that DC motors/thrusters draw most of power. Various magnet volume and torque usually give different results [17,18]. For Tech_SAS ROV, 12V/1.3A 1100 GPH bilge pump is chosen and modified into water-proofed DC motor as a thruster [19,20].…”
Section: Tether Cable Designmentioning
confidence: 99%
“…This table also has shown that DC motors/thrusters draw most of power. Various magnet volume and torque usually give different results [17,18]. For Tech_SAS ROV, 12V/1.3A 1100 GPH bilge pump is chosen and modified into water-proofed DC motor as a thruster [19,20].…”
Section: Tether Cable Designmentioning
confidence: 99%
“…In [8][9][10][11][12][13], the schemes based on the improved chattering-free sliding mode control (SMC) are used to control the underwater robot system with the unmodeled uncertainties and external disturbances. In [14][15][16][17][18][19][20][21][22][23], the adaptive control schemes designed on the particular structure of the underwater robot are used to realize the trajectory tracking control with system disturbances. In [24,25], the adaptive backstepping control schemes are designed by an inverse procedure of making system robust stable which is used to make the UVMS track the desired trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Often called telemanipulators, these devices are usually deployed to worksites onboard support base vehicles which are also remotely operated—therefore referred to as Remotely Operated Vehicles (ROVs). Work-class ROV technology has served subsea Intervention, Repair, and Maintenance (IRM) operations in various offshore industries, including oil and gas, marine construction, marine science, naval defence, and Marine Renewable Energy (MRE) [ 1 , 2 , 3 ]. Submarine work-class ROVs are generally equipped with two manipulators; one dexterous seven function manipulator that is used to perform the actual intervention task, and one simple, powerful grabber that is used to hold the ROV stationary relative to the structure on which the operation is taking place.…”
Section: Introductionmentioning
confidence: 99%